Exploring informal workplace learning in primary healthcare for continuous professional development. Issue 4 (4th July 2017) - Joynes, Viktoria; Kerr, Micky; Treasure-Jones, Tamsin
Abstract: Background and objectives : All health and social care professionals learn on the job through both formal and informal learning processes, which contributes to continuous professional development (CPD). This study explored workplace learning in General Practices, specifically looking at the role of informal learning and the workplace practices that appear to support or restrict that learning, as well as how technology was integrated into these learning processes. Methods : Three focus groups with general practitioners, practice nurses, managerial and administrative staff were conducted followed by twelve individual semi-structured interviews with participants drawn from the focus groups. Three observations of multi-disciplinary team meetings were used to establish potential team-based learning activities. Results : Triggers for informal workplace learning included patients presenting challenging or unusual conditions; exposure to others' professional practice; and policy driven changes through revised guidance and protocols. By exploring how these triggers were acted upon, we identified mechanisms through which the primary care workplace supports or restricts informal learning through working practices, existing technologies and inter-professional structures. Conclusion : Informal workplace learning was identified as arising from both opportunistic encounters and more planned activities, which are both supported and restricted through a variety of mechanisms. Maximising informal learning opportunities and removing barriers to doing so should be a priority for primary care practitioners, managers and educators.